Pendidikan Karakter Melalui Pembelajaran Bahasa dan Sastra Menggunakan Cerita Rakyat Kutai Ayus dan Ongo - Nur, Muhammad Ma'rifan; Mulawarman, Widyatmike Gede; Siddik, Mohammad (PT Literasi Nusantara Publisher, 2025)
This study aims to describe the values of character education found in the Kutai folktales Ayus and Ongo and examine their relevance in language and literature learning at school. The research employed an ethnographic approach, utilizing observation and interviews to explore oral traditions. The findings reveal that the folktales contain character values such as courage, responsibility, hard work, religiosity, and social awareness. These stories, presented as legends and fairy tales, predominantly portray positive role models suitable for educational purposes. The character values identified are relevant to literature instruction as they contribute to students’ character formation. Therefore, the Ayus and Ongo folktales can serve as contextual learning materials to strengthen character education in schools, particularly in the teaching of Indonesian language and literature.